Narrative Inquiry into STEM Learning: Humanizing Science and Mathematics Education through Stories - Mohammad Ali; Evvy Lusyana; Reza Karimi (International Journal of Educational Narratives, 2025)
Background. STEM education has traditionally emphasized technical proficiency and cognitive mastery, often overlooking the human, emotional, and ethical dimensions of learning. This study explores how narrative inquiry can serve as a humanizing framework for science and mathematics education by integrating personal stories, lived experiences, and reflective dialogue into STEM classrooms. Purpose. The research aims to examine how narratives influence students’ conceptual understanding, engagement, and sense of identity within STEM learning environments. Method. Using a qualitative narrative inquiry design, data were collected from classroom observations, reflective journals, and in-depth interviews with teachers and students across three interdisciplinary STEM programs. Results. The findings reveal that storytelling fosters empathy, curiosity, and deeper conceptual comprehension by connecting abstract scientific concepts to real-world experiences. Teachers reported that narrative integration enhanced collaboration and critical thinking, while students demonstrated increased ownership of learning and appreciation for the human relevance of STEM subjects. Conclusion. The study concludes that narrative-based STEM education bridges the gap between technical knowledge and human experience, cultivating reflective, ethical, and socially conscious learners. Narrative inquiry thus repositions STEM not only as a field of innovation but also as a domain of meaning, emotion, and shared human inquiry.